Ferroelectricity in Si‐Doped HfO2 Revealed: A Binary Lead‐Free Ferroelectric. (28th October 2014) - Martin, Dominik; Müller, Johannes; Schenk, Tony; Arruda, Thomas M.; Kumar, Amit; Strelcov, Evgheni; Yurchuk, Ekaterina; Müller, Stefan; Pohl, Darius; Schröder, Uwe; Kalinin, Sergei V.; Mikolajick, Thomas
<x xml:space="preserve">Abstract</x> Static domain structures and polarization dynamics of silicon doped HfO2 are explored. The evolution of ferroelectricity as a function of Si‐doping level driving the transition from paraelectricity via ferroelectricity to antiferroelectricity is investigated. Ferroelectric and antiferroelectric properties can be observed locally on the pristine, poled and electroded surfaces, providing conclusive evidence to intrinsic ferroic behavior. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>